PENGARUH FREE CASH FLOW, PROFITABILITAS, DAN KEPEMILIKAN MANAJERIALTERHADAP KEBIJAKAN HUTANG PERUSAHAAN - Satiti, Lufiana; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to examine the influence of free cash flow, profitability, and managerial ownership to the debt policy of manufacturing companies in consumption goods sector which are listed in Indonesia Stock Exchange.The population is manufacturing companies in consumption goodssector which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. the sample collection has been done by using purposive sampling and based on the predetermined criteria, 15 manufacturing companies have been selected as samples with the amount of research observation is 75 observations.The result of the research shows that free cash flow gives significant positive influence to the debt policy. It shows that high free cash flow will increase company debt.Becausehigh free cash flow will make the stockholders desire to share it in the form of dividend. Profitability give significant and negative influence to the company debt policy. It shows that the high profit which has been obtained by the company will make the level of company debt low, because the high profit is used to fulfill the operational needs and company investment. Meanwhile, the managerial ownership does not give any influence to the debt policy. It reflects that the public company managers are not the defining factor in Indonesia in the making of funding decision policy from debt because the amount of managerial ownership is lower than the amount of institutional ownership in the company.Keywords: free cash flow, profitability, managerial ownership, debt policy.